Filipino-Based Learning Activity Sheets (LAS): Impacts on Grade 10 Students' Conceptual Understanding of Plate Boundaries and Earthquake - Cajurao, Erdee C; Cajurao, Irene P.; Romero, Junan N.; Bolivar, Janna T.; Diestro, Juvy L.; Merida, Mona Cris E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aimed to examine the impacts of Filipino-based Learning Activity Sheets (LAS) on Grade 10 students' conceptual understanding of plate boundaries and earthquakes in science under the modular distance learning modality. Using a pre-experimental one-group pretest-posttest design, 30 students from Tomas V. Rivera National High School in Cawayan, Masbate were randomly selected to participate in the study. The results showed a significant improvement in students' conceptual understanding of plate boundaries and earthquakes, with a positive mean gain of 6.8 and 7.1, respectively, from the pretest to the posttest scores. Specifically, the students' level of conceptual understanding improved from 23.7% to 96.8%, with a 97% correct response rate on the posttest results. Moreover, paired sample t-test analysis revealed that the posttest scores of the students were significantly higher than their pretest scores at the 5% level of significance. These findings suggest that Filipino-based LAS significantly enhances students' conceptual understanding and mastery of concepts related to plate boundaries and earthquakes in Grade 10 Science under modular distance learning mode.